2018
DOI: 10.1016/j.ejphar.2018.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase-3 inhibitor cilostazol reverses endothelial dysfunction with ageing in rat mesenteric resistance arteries

Abstract: Ageing impairs endothelial function, which is considered a hallmark of the development of cardiovascular diseases in elderly. Cilostazol, a phosphodiesterase-3 inhibitor, has antiplatelet, antithrombotic and protective effects on endothelial cells. Here, we hypothesized that cilostazol could improve endothelial function in mesenteric resistance arteries (MRA) from old rats. Using eight-week cilostazol-treated (100mg/kg/day) or untreated 72-week-old Wistar rats, we evaluate the relaxation to acetylcholine, sodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…Contemporary research using a rat model suggests that cilostazol can improve age-related endothelial dysfunction via suppression of oxidative stress, increased bioavailability of nitric oxide, and EDHF-like vasorelaxation. Cilostazol treatment has also been shown to be effective in preventing the development of atherosclerosis by downregulating the expression of cytokines and chemokines induced by glucose [31]. In the present study, we demonstrate for the first time to our knowledge, that cilostazol can inhibit activation of the proinflammatory NLRP3 inflammasome induced by high FFA exposure, thereby significantly suppressing endothelial dysfunction due to chronic inflammation and oxidative stress.…”
Section: Discussionsupporting
confidence: 57%
“…Contemporary research using a rat model suggests that cilostazol can improve age-related endothelial dysfunction via suppression of oxidative stress, increased bioavailability of nitric oxide, and EDHF-like vasorelaxation. Cilostazol treatment has also been shown to be effective in preventing the development of atherosclerosis by downregulating the expression of cytokines and chemokines induced by glucose [31]. In the present study, we demonstrate for the first time to our knowledge, that cilostazol can inhibit activation of the proinflammatory NLRP3 inflammasome induced by high FFA exposure, thereby significantly suppressing endothelial dysfunction due to chronic inflammation and oxidative stress.…”
Section: Discussionsupporting
confidence: 57%
“…Cilostazol, a selective PDE-III inhibitor, acts as a vasodilator and antithrombotic antiplatelet agent, and it has been shown to promote lower triglyceride levels and increase HDL in patients with PAOD [22], to improve postprandial lipemia in patients with diabetes [13], to increase nitric oxide (NO) expression with a positive effect on apoptosis [23], to prevent thrombosis after stenting [24], and to have the ability to ameliorate atherosclerotic progression [25]. Cilostazol has also been reported to cause the accumulation of cAMP in VSMCs, resulting in the upregulation of antioncogenes p53 and p21 and hepatocyte growth factor [26].…”
Section: Discussionmentioning
confidence: 99%
“…EDHF plays a central role in the regulation of endothelial function for vasodilation and coordination of blood flow in the vasculature 10. The EDHF-mediated response is altered with aging, hypertension, diabetes, and hypoxia-reoxygenation injury 9,11,12,22. These alterations may either contribute to endothelial dysfunction or compensate for the loss of NO bioavailability, depending on the vascular bed 10.…”
Section: Discussionmentioning
confidence: 99%
“…EDHF plays an important role in the regulation of vascular tone, and impaired EDHF has been associated with endothelial dysfunction 10. Increasing evidence has shown that EDHF-mediated vasodilation decreases with aging, hypertension, and diabetes 9,11,12…”
Section: Introductionmentioning
confidence: 99%